HISTOPATHOLOGICAL ALTERATIONS IN TESTES ON. CHRONIC DERMAL EXPOSURE OF CYPERMETHRIN IN WISTAR RATS - VERMA, P K; RAO, M MUTHA; SRILATHA, CH; RAINA, R (The Indian Journal of Animal Reproduction, 2010)
The effect of chronic dermal exposure of cypermethrin on the testicular tissue in Wistar rats (n=18) was studied. Multiple small to large vacuolation and necrosis in the epithelial lining of seminiferous tubules, eosinophilic secretions in interstitium and presence of single or multiple giant cell in the lumen of tubules were seen. The changes were found to be exposure dependant. These observations suggest that chronic dermal exposure of cypermethrin cause degenerative changes in seminiferous tubules of rat testes.